The biology and control of an emerging shield bug pest, Pentatoma rufipes (L.) (Hemiptera: Pentatomidae). (27th August 2020) - Powell, Glen
Abstract : Pentatoma rufipes (L.) is common and widespread across much of the Palaearctic. The insect is particularly associated with deciduous trees and may remain in woodlands throughout the year, feeding on species such as oak, beech, and hazel. Pentatoma rufipes is emerging as an important pest of tree fruit in northern Europe. In recent years, agronomists have been finding increasing numbers of P. rufipes in and around orchards. Feeding activity on developing fruits is being linked with pitting and distortion damage to crops including apples and pears. There has been limited research into the ecology of this pest. Crops are particularly susceptible shortly after flowering, when over‐wintered P. rufipes nymphs feed on developing fruit. Limited information is available linking local population levels and activity with damage. There has been some research on the impact of control strategies, but the most effective product tested was a broad‐spectrum pyrethroid insecticide. Assessments of more selective plant protection products and the availability of alternative control strategies would help develop more integrated and effective control programmes for this pest. This review highlights several key findings concerning the biology and control of the pest and makes specific recommendations for further research.